Becoming greener – digitalization in my work. International Week 10.–14.2.2020 - Mirola, Tuuli; fi=LAB-ammattikorkeakoulu|sv=LAB-ammattikorkeakoulu|en=LAB University of Applied Sciences| (LAB University of Applied Sciences, 2020)
The first international week of LAB University of Applied Sciences was organized in Lappeenranta on 10.-14.2.2020. This year the theme for the International Week publication is “Becoming greener – digitalization in my work”. The authors of the articles in this publication are sharing their personal experiences and practical examples of digitalization in education. This publication addresses the topic of our International Week from various points of view. The articles offer us examples from multiple counties and partner universities on different fields of education. Educational aspects are presented for example from the point of view of language and communication courses and engineering. The authors also share their experiences, research and practices on various fields of business such as transports, architecture and construction, real estate markets, healthcare, tourism and hospitality business.